Current Knowledge on the Function of α-Methyl Acyl-CoA Racemase in Human Diseases - Kong, Gyeyeong; Lee, Hyunji; Tran, Quangdon; Kim, Chaeyeong; Park, Jisoo; Kwon, So Hee; Kim, Seon-Hwan; Park, Jongsun (Frontiers in Molecular Biosciences, 2020)
Branched chain fatty acids perform very important functions in human diet and drug metabolism. they cannot be metabolized in mitochondria and are instead processed and degraded in peroxisomes due to the presence of methyl groups on the carbon chains. Oxidative degradation pathways for lipids include α- and β-oxidation and several pathways. In all metabolic pathways, α-methyl acyl-CoA racemase (AMACR) plays an essential role by regulating the Metabolism and lipid of drugs. AMACR regulates β-oxidation of branched chain lipids in peroxisomes and mitochondria and promotes chiral reversal of 2-methyl acids. AMACR defects cause sensory-motor neuronal and liver abnormalities in humans. These phenotypes are inherited and are caused by mutations in AMACR. In addition, AMACR has been found to be overexpressed in prostate cancer. In addition, the protein levels of AMACR have increased significantly in many types of cancer. Therefore, AMACR may be an important marker in tumors. In this review, a comprehensive overview of AMACR studies in human disease will be described.